2011
DOI: 10.1001/archsurg.2011.273
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Very Low-Calorie Diet and Operative Outcome After Laparoscopic Gastric Bypass

Abstract: Hypothesis: A 14-day very low-calorie diet (VLCD) regimen before a laparoscopic gastric bypass procedure will improve perioperative and postoperative outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
157
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 206 publications
(162 citation statements)
references
References 27 publications
2
157
0
3
Order By: Relevance
“…Several studies 17,[19][20][21] demonstrate the effectiveness of preoperative all-liquid meal-replacement diets, which provide greater control over caloric and nutritional intake. All-liquid diets tend to deliver fewer calories than conventional diets, reducing the length of time required to meet particular preoperative weight loss goals.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies 17,[19][20][21] demonstrate the effectiveness of preoperative all-liquid meal-replacement diets, which provide greater control over caloric and nutritional intake. All-liquid diets tend to deliver fewer calories than conventional diets, reducing the length of time required to meet particular preoperative weight loss goals.…”
mentioning
confidence: 99%
“…26 Thus, conclusions cannot be drawn from this report. Finally, one additional randomized trial was conducted by Van Nieuwenhove et al, 21 but included only a 30-day follow-up. This trial reported no difference in postoperative weight loss between RYGB patients losing weight (4.9 ± 3.6 kg) preoperatively on an 800 kcal per day all-liquid meal diet vs control.…”
mentioning
confidence: 99%
“…In a reanalysis with 12-month follow-up of the same study, Solomon et al (17) reported statistically significant improvement in body weight, BMI, and EBWL when patients who lost >5% EBW preoperatively were compared with those who did not. In the other rCT published, van nieuwenhove et al (12) reported no difference in weight loss 3 months after gastric bypass in patients randomized to preoperative vLCD (Modifast ® 800 kcal/day) compared to patients allocated to no preoperative diet regimen. However, 3 months is too short follow-up in order to make any conclusions, and the study was not designed to address this issue.…”
Section: Postoperative Weight Lossmentioning
confidence: 97%
“…In both of these, participating surgeons scored visibility as being improved after weight loss, although these were blinded to treatment allocation in only one study (12). Moreover, Alami et al (18) reported that estimated liver volume was reduced in patients who were successful in losing weight preoperatively, which further support the potential for this regimen to reduce technical complexity during bariatric surgery.…”
Section: Intraoperative Outcomesmentioning
confidence: 99%
“…Pour les auteurs du consensus français, cet amaigrissement est inutile car il n'influence ni la mortalité, ni l'incidence des complications postopératoires, ni la perte de poids à long terme [29]. Cependant, deux études publiées récemment vont un peu à l'encontre de ces recommandations et préconisent au contraire un amaigrissement préopératoire chez le sujet obèse avant chirurgie bariatrique, même si les résultats objectifs de la perte de poids préopéra-toire (réduction de la perception de la difficulté de la procédure chirurgicale) demeurent modestes [30,31]. Le débat reste donc ouvert à l'heure actuelle.…”
Section: Recommandationsunclassified